Probable Maximum Precipitation Estimation Using Statistical Approach - Ismail, Nurul Jannah (Universiti Sains Malaysia, 2017)
Probable Maximum Precipitation (PMP) is defined as the greatest depth of precipitation for a given time and duration over a given storm area or watershed area under meteorological conditions. The PMP for stations in Malaysia by Hershfield statistical method in earlier studies was estimated using frequency factor of 15 which is the highest value in the world. The value of 15 as frequency factor was found to be too high for a humid country like Malaysia. In this study, annual maximum 1-day rainfall data of about 30 years for four stations which consist of three stations on the eastern and one on western part of Peninsular Malaysia were analysed in an attempt to estimate PMP for 1-day duration based on an appropriate frequency factor. The stations are situated at Setor JPS Kuala Terengganu, Terengganu, Stn. Pertanian Melor at Kota Bharu, Kelantan, Paya Besar at Kuantan, Pahang and Ldg. Batu Untong at Kuala Langat, Selangor. Comparisons of the PMP estimate based on the statistical approach of Hershfield (1965) were analysed with the PMP values computed using the Conventional method of the statistical approach. From this study, it was found that PMP estimates by Hershfield method can produce reasonable PMP estimates and is valid for subsequent design calculations and conventional method is comparable to the Hershfield method and have produced more conservative results by performing quick statistical analysis. Both of the methods discussed have proven to be useful for PMP estimations when practice carefully. Hence, the use of statistical approach is regarded as acceptable for computation of PMP estimates. Based on the actual rainfall data of the stations, the highest value of the frequency factor was found to be 14 for Ldg. Batu Untong, 13 for Setor JPS Kuala Terengganu and 12 for both Stn. Pertanian Melor and Paya Besar.